IDENTIFICATION OF FISHERY RESOURCES IN MADURA STRAIT BASED ON THE IMPLEMENTATION OF POTENTIAL FISHING ZONE INFORMATION FROM REMOTE SENSING - Bidawi Hasyim; Maryani Hartuti; Sayidah Sulma (BRIN, 2009)
Spatial information of Potential Fishing Zone (PFZ) was used to identify the prospective location in the Madura Strait, where the fishermen from Fish Landing Port (FLP) around the Madura Strait conducted fishing activities. PFZ was aimed to determine fishing location, to identify the type of pelagic fish resources which were dominantly caught in the MAdura Strait. Fish resources data were obtained by observing the FLP in the east of Madura Strait especially in Pondok Mimbo, Jangkar, Besuki, Probolinggo, Pamekasan, and Sumenep. Based on the application of PFZ spatial information and observation, the types of pelagic fish caught on west monsoon were dominated by Euthynnus spp, Decapterus spp, Ratsrellinger spp, and Trichiurus spp. In the first transition season, types of fish resources were a mix between Euthynnus spp, Decapterus spp, Rastrellinger spp, Sardinella longiceps, and Trichiurus spp, however Sardinella longiceps were still dominated the catches. During the east monsoon fish resources at the Madura Strait was also dominated by Sardinella longiceps. This condition occurred until the second month of the second transition season followed by the mixing among Sardinella longiceps, Euthynnus spp, Decapterus spp, Rastrellinger spp and Trichiurus spp. Keywords: Fish Landing Port, NOAA-AVHRR, Potential fishing zone